EFFECTIVENESS OF THE DIGITAL IMAGE LIBRARY CASES IN HUMAN ANATOMY STUDIES - Kazoka, Dzintra; Pilmane, Mara (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In several education technologies and options for teaching and studies one of the alternatives is the Anatomage 3D virtual dissection table with included Digital Image Library. The aim of this study was to observe the effectiveness of the Digital Image Library cases in Human Anatomy studies at Rīga Stradiņš University (RSU). In 2017 it was used every second week during the autumn`s practical classes on several occasions to show variety of interesting and many unique human anatomy cases, abnormalities, diseases and detailed sectional scans. As methods for collecting data were used discussions between students groups and survays. The sample included 100 students and 1 Human Anatomy tutor. The findings suggest that the Digital Image Library cases are very interactive and effective tools of the teaching and studies in Human Anatomy at RSU. This is a new form of the communication between students, tutor, virtual reality of the body systems and it provides a lot of digital materials that develop relationships between basic and clinical study subjects.